1999
DOI: 10.3102/01623737021002097
|View full text |Cite
|
Sign up to set email alerts
|

Tennessee's Class Size Study: Findings, Implications, Misconceptions

Abstract: After years of debate, speculation, and research, Tennessee's Project STAR produced clear answers to the question, “Do small classes result in improved academic achievement in the elementary grades?” This article describes the features that made STAR unique and summarizes the findings with regard to pupil performance and behavior. New analyses show the magnitudes of the “small-class advantage” during and after the 4-year experimental period. The positive findings of STAR have been greeted with enthusiasm by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
3
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(159 citation statements)
references
References 28 publications
7
141
3
5
Order By: Relevance
“…Tennessee's Project Star included 79 schools and 329 classrooms (Finn & Achilles, 1999). All participating schools had space to create additional classrooms, additional teachers were by and large available to staff the classes, and the state provided funds to hire the additional teachers.…”
Section: Additional Human Economic and Physical Resources And Theirmentioning
confidence: 99%
“…Tennessee's Project Star included 79 schools and 329 classrooms (Finn & Achilles, 1999). All participating schools had space to create additional classrooms, additional teachers were by and large available to staff the classes, and the state provided funds to hire the additional teachers.…”
Section: Additional Human Economic and Physical Resources And Theirmentioning
confidence: 99%
“…By the end of fifth grade, small class students were about 5 months (about a half of a school year) ahead of larger class students in literacy, math, science, and study skills (Finn & Achilles, 1999). In sum, a number of analyses of the STAR data have produced several arguments in favor of reducing class sizes for elementary school students.…”
Section: Research On Class Size Effectsmentioning
confidence: 98%
“…Class size and teacher-pupil ratio are two entirely different constructs. As Finn and Achilles (1999) write, "they represent different aspects of resource distribution among schools and should not be used interchangeably." The substitution of pupil-teacher ratio for class size may weaken the treatment effects, as class sizes are invariably higher than the teacher-pupil ratios.…”
Section: Research On Class Size Effectsmentioning
confidence: 99%
“…In a summary of all empirical evidence available until 1994, including 277 estimates from 59 rigorous studies of the impact of class size on academic achievement, Hanushek (1999) reported that only 15% of all studies presented significant positive estimates of impact, while 13% of studies presented significant negative estimates-a pattern most likely to represent a null effect of the policy. Experimental evidence from the Student/Teacher Achievement Ratio, or STAR, experiment (Finn & Achilles, 1999;Hanushek, 1999;Krueger, 1999) indicated that performance on standardized tests increased significantly for students in small classes compared to students in regular classes, particularly after just one year of class size intervention (Krueger, 1999). Other studies exploring natural class size variation have demonstrated that reductions of 30 to 15 students did not have a significant impact on student performance on state tests (Hoxby, 1998(Hoxby, , 2000.…”
Section: Impact Of Class Size and Composition Policiesmentioning
confidence: 99%
“…The best way to solve this empirical problem would be to randomly assign schools that applied to the program to PMSE or a comparison group, and then evaluate their outcomes, as was the case with the Student/Teacher Achievement Ratio, or STAR, experiment (Finn & Achilles, 1999;Hanushek, 1999;Krueger, 1999). However, because randomization is not applicable to programs already at scale, such as PMSE, researchers have applied econometric techniques that take advantage of the natural variation in educational processes to achieve estimates of the true impact of class size policies (Angrist & Lavy, 1999;Dobbelsteen et al, 2002;Hoxby, 1998Hoxby, , 2000McEwan & Urquiola, 2005).…”
Section: Evaluating Policy and Program Impactmentioning
confidence: 99%